No impact of KIF6 genotype on vascular risk and statin response among 18,348 randomized patients in the heart protection study. - Hopewell, J; Parish, S; Clarke, R; Armitage, J; Bowman, L; Hager, J; Lathrop, M; Collins, R (2011)
OBJECTIVES: The aim of this study was to test the effects of the KIF6 Trp719Arg polymorphism (rs20455) on vascular risk and response to statin therapy in 18,348 participants from the Heart Protection Study. BACKGROUND: There have been claims that noncarriers of the KIF6 719Arg variant receive little benefit from statin therapy. Screening for this genetic variant is now being used to influence statin use. METHODS: Participants received 40 mg simvastatin daily for 4 to 6 weeks before being randomly allocated 40 mg simvastatin daily or placebo for 5 years. Major coronary event was pre-defined as coronary death or nonfatal myocardial infarction, and major vascular event was pre-defined as major coronary event plus revascularization or stroke. RESULTS: The KIF6 genotype was not significantly associated, among placebo-allocated participants, with the risks of incident major vascular events, major coronary events, revascularizations, or strokes. Overall, 40 mg simvastatin daily produced a 42% reduction in low-density lipoprotein cholesterol, which did not differ significantly by KIF6 719Arg carrier status (p = 0.51). Proportional reductions in the risk of major vascular events with statin therapy were similar (interaction p = 0.70) and highly significant across KIF6 genotypes: 23% (95% confidence interval: 16% to 29%; p = 5.3 × 10⁻¹⁰) in carriers (Arg/Arg or Trp/Arg), and 24% (95% confidence interval: 17% to 31%; p = 4.6 × 10⁻⁹) in noncarriers (Trp/Trp). A similar lack of interaction was observed for major coronary events, revascularizations, and strokes considered separately. CONCLUSIONS: Statin therapy significantly reduces the incidence of coronary and other major vascular events to a similar extent, irrespective of KIF6 genotype. Consequently, the use of KIF6 genotyping to guide statin therapy is not warranted. (Heart Protection Study; ISRCTN48489393).